Pengembangan Wisata Danau Letang dalam Upaya Peningkatan Ekonomi Masyarakat di Kabupaten Batanghari - Ovie Yanti; Musyaiyadah Musyaiyadah (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
Batanghari Regency has quite a lot of tourism potential that can be developed, such as an exotic urban forest atmosphere, a lake surrounded by bushes and a cool and comfortable atmosphere, making it a special attraction for visitors. The plan to develop tourism potential in Batanghari Regency has been ongoing for a long time. However, this arrangement has only been implemented since 2021. The Batanghari Regency Government is committed to making tourism in Batanghari Regency a combination of beautiful and unique nature with local cultural wisdom to improve the economy of the community. This research describe the development of tourism potential in improving the community economy in Batanghari Regency and identify the obstacles faced. This research takes a qualitative approach. Data collecting methods included observation, interviews, and documentation. The data obtained in this research were analyzed using the interactive model proposed by Miles also Huberman, This comprises data reduction, presentation, and making conclusions.